The effect of athletes' training satisfaction on competitive state anxiety—a chain-mediated effect based on psychological resilience and coping strategies - Yu, Xiaomei; Yang, Yang; He, Bo (Frontiers in Psychology, 2024)
Introduction: This study aimed to investigate the relationship between athletes' training satisfaction and competitive state anxiety, by examining the mediating roles of psychological resilience and coping strategies. The findings provide a theoretical foundation and practical recommendations for enhancing athletes' training and mental health services. Methods: A questionnaire was utilized to assess training satisfaction, psychological resilience, coping strategies, and Competitive State Anxiety among a sample of 447 athletes. The data was examined through descriptive statistics, correlation analysis, and structural equation modeling, employing SPSS and the Process 3.5 plug-in. Results: Training satisfaction had a significant positive effect on psychological resilience (β=0.726, p<0.001), while training satisfaction (β=0.178, p<0.001) and psychological resilience (β=1.138, p<0.001) were found to have a significant positive effect on strategy. Additionally, training satisfaction, psychological resilience, and coping strategies all demonstrated a significant negative effect on competitive state anxiety (p<0.001). Training satisfaction indirectly influenced competitive state anxiety through psychological resilience (indirect effect 1), coping strategies (indirect effect 2), and the combined mediating effect of psychological resilience and coping strategies (indirect effect 3), resulting in a total indirect effect of -0.385 (95% CI=[-0.433, -0.337]). Discussion: In conclusion, enhancing athletes' training satisfaction can help reduce competitive state anxiety by improving psychological resilience and fostering positive coping mechanisms.